Leptomeningeal enhancement in computed tomography of feline brains - Babicsak, Viviam Rocco [UNESP] (2011)
Contrast enhancement enables the verification of several pathological conditions that lead to vascular changes and/or breakdown of the blood-brain barrier. Examples of diseases that cause these disorders are: neoplastic diseases, vascular communications, active inflammation and cerebral ischemia. Several contrast enhancements located peripherically to cerebral lobes, in the topography of brain sulci and gyri, were identified on tomographic scan of twelve healthy cats that had their health confirmed through history, general and neurologic physical examination and polymerase chain reaction for feline leukemia (FeLV) and immunodeficiency (FIV) virus. This study aims to describe the tomographic contrast enhancement findings, which showed an identical appearance to the pia mater and arachnoid enhancement, also called leptomeninges. This finding is generally considered related to leptomeningeal diseases such as meningitis and neoplastic disease. However, in dogs, the leptomeningeal enhancement has already been described in healthy animals. This finding has a great importance in the interpretation of tomographic images of these animals since, so far, in the presence of these enhancements, meningeal disorders were suggested. Thus, the verification of other tomographic findings and the combination with other diagnostic methods are of great importance for the diagnosis of leptomeningeal disease.